2013
DOI: 10.3109/09513590.2013.829447
|View full text |Cite
|
Sign up to set email alerts
|

Menarche, puberty and psychiatric disorders

Abstract: This study underlies the puberty and adolescence period for psychiatric illness. An integrative clinical approach is suggested while examining the psychiatric illness at the basis of engaged roles of hormonal effects of menarche, social effect of puberty psychiatric complaints and genetical and psychosocial burden of family story of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Likewise, ADHD is known to lead to a loss of functionality in both the child and the family. In previous studies, adolescents who have more conflicts with their families have been shown to experience an earlier occurrence of BD (31). In this respect, the results of our study indicate that each behavioral, etiologic, and communication-related aspect of the affective temperaments should be researched in terms of both ADHD and bipolarity.…”
Section: Discussionsupporting
confidence: 56%
“…Likewise, ADHD is known to lead to a loss of functionality in both the child and the family. In previous studies, adolescents who have more conflicts with their families have been shown to experience an earlier occurrence of BD (31). In this respect, the results of our study indicate that each behavioral, etiologic, and communication-related aspect of the affective temperaments should be researched in terms of both ADHD and bipolarity.…”
Section: Discussionsupporting
confidence: 56%
“…It should be taken into account that stress in adolescent girls has been implicated in increased prevalence of depression and anxiety disorders. Integrative clinical approach is suggested while examining pubertal psychiatric complaints and genetical and psychosocial aspects should be taken into consideration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that hormonal changes could pave the way to mood disorders [2,3]. Estrogen and testosterone are known to be mood elevators [4].…”
Section: Introductionmentioning
confidence: 99%